Ferroptosis resistance in cancer cells: nanoparticles for combination therapy as a solution - Adzavon, Kodzo Prosper; Zhao, Weijian; He, Xuesong; Sheng, Wang (Frontiers in Pharmacology, 2024)
Ferroptosis is a form of regulated cell death (RCD) characterized by iron-dependent lipid peroxidation. Ferroptosis is currently proposed as one of the most promising means of combating tumor resistance. Nevertheless, the problem of ferroptosis resistance in certain cancer cells has been identified. This review first, investigates the mechanisms of ferroptosis induction in cancer cells. Next, the problem of cancer cell resistance to ferroptosis, as well as the underlying mechanisms is discussed. Recently discovered ferroptosis-suppressing biomarkers have been described. The various types of nanoparticles that can induce ferroptosis are also discussed. Given the ability of nanoparticles to combine multiple agents, this review proposes nanoparticle-based ferroptosis cell death as a viable method of circumventing this resistance. This review suggests combining ferroptosis with other forms of cell death, such as apoptosis, cuproptosis and autophagy. It also suggests combining ferroptosis with immunotherapy.